2012
DOI: 10.1111/j.1476-5381.2012.01855.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural and synthetic modulators of SK (Kca2) potassium channels inhibit magnesium‐dependent activity of the kinase‐coupled cation channel TRPM7

Abstract: BACKGROUND AND PURPOSETransient receptor potential cation channel subfamily M member 7 (TRPM7) is a bifunctional protein comprising a TRP ion channel segment linked to an a-type protein kinase domain. TRPM7 is essential for proliferation and cell growth. Up-regulation of TRPM7 function is involved in anoxic neuronal death, cardiac fibrosis and tumour cell proliferation. The goal of this work was to identify non-toxic inhibitors of the TRPM7 channel and to assess the effect of blocking endogenous TRPM7 currents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
135
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 83 publications
6
135
0
Order By: Relevance
“…The previously reported TRPM7 block by NS8593 exhibited a mild dependence on intracellular Mg 2+ (IC 50  = 1.6 µM without Mg 2+ ; 5.9 µM at 300 µM Mg 2+ ) [18]. In addition, high intracellular Mg 2+ inhibits the TRPM7 current in microglia [19] and other cells [48], [49].…”
Section: Resultsmentioning
confidence: 73%
“…The previously reported TRPM7 block by NS8593 exhibited a mild dependence on intracellular Mg 2+ (IC 50  = 1.6 µM without Mg 2+ ; 5.9 µM at 300 µM Mg 2+ ) [18]. In addition, high intracellular Mg 2+ inhibits the TRPM7 current in microglia [19] and other cells [48], [49].…”
Section: Resultsmentioning
confidence: 73%
“…In particular, mitochondrial ROS dependent-TRPM2 activation was shown to mediate liposome/particulate induced NLRP3 inflammasome activation (65). We observed that neither the broad TRP channel inhibitor ruthenium red nor the selective TRPM7 inhibitor NS8593 (66, 67) suppressed NG- or TcdB-induced pyroptotic propidium 2+ uptake (Fig 7F,G). In another recent study (68), we reported that Trpm2 −/− BMDC stimulated with NG did not exhibit reduced propidium 2+ influx compared to that in WT cells.…”
Section: Resultsmentioning
confidence: 90%
“…TRPM7 is permanently blocked by divalent cations, but when patched with Mg 21 -free pipette solution, switching to a bath solution lacking Ca 21 and Mg 21 ions gives rise to large inward and outward currents (Nadler et al, 2001). Because TRPM7-like currents exhibit a fast rundown when using a Na 1 -based bath solution, we used a Cs 1 -based bath solution, as described elsewhere (Chubanov et al, 2012). Neither isosakuranetin nor liquiritigenin (20 mM each) affected TRPM7-dependent inward or outward currents in HEK293 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%